Effect of Dietary Probiotic Supplementation on Performance, Gut Microflora, and Hematology of Local Quails - Rebin A. Mirza (Polytechnic Journal)
This research was conducted to evaluate the effect of probiotic supplementation on growth performance, gut microbiota, and hematology of local quails. Ninety-one-week-old quails were randomly distributed into three dietary treatments with three replicate per each for 42 days. The dietary treatments were: Treatment 1 which was control (no additive), standard diet added with Lactobacillus animalis bacteria 1 g/kg 1.35 × 109 colony forming units (CFU)/kg (PRO1) and commercial multi-strain probiotic (Lactobacillus acidophilus 2.75 × 1010 CFU, Streptococcus faecium 8.25 × 1010 CFU, and Bacillus subtilis 1.1 × 1010 CFU) (PRO2). Results showed that PRO1, isolated from chicken caeca, had probiotic properties to improve growth performance of local quail compared to the control group. In cecum digesta, addition of both types of probiotics significantly increased the number of Lactobacillus spp. and reduced the number of coliform bacteria at the end of the experiment. Furthermore, supplementation of both types of probiotics significantly increased the number of lymphocyte and reduced H/L ratio compared to the control group at the end of the experiment. While, no significant differences were observed between both types of probiotic. This research has established that L. animalis, which isolated in cecum of chicken origin, had the same data recorded when compared to commercial multi-strain bacteria probiotic by improved growth performance, gut microbiota, and hematology parameters and could be a convenient probiotic additive in dietary local quail.